Resource sector concessions and spatial development in Southern Africa - Joan Halstein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper explores how Southern Africa can leverage its mineral resources to support growth and industrialization. It considers the aggregate and spatial effects of transport infrastructure improvements, and the relative benefits of financing these investments through resource sector concessions versus government expenditure. Using computable general equilibrium analysis, this paper simulates and compares the effects of (1) royalty rebates for infrastructure; (2) zero royalties for infrastructure; and (3) government revenue-financed infrastructure improvements in South Africa and the rest of Southern Africa. The findings suggest that infrastructure directly financed through government royalty revenue has stronger spatial and aggregate effects than concession-based investments. Nonetheless, concession-based investments are less distortionary and crowd-in private investments. Infrastructure improvements, regardless of the method of financing, stimulate activity in non-mining sectors, but sectoral changes are significantly different for South Africa and the rest of Southern Africa. The choice of financing depends on the objectives of the implementing government.
Keywords: D58; F21; Q32; R53; 330; computable general equilibrium; infrastructure; resource sector